Diverse and reprogrammable mechanisms of malignant cell transformation in lymphocytes: pathogenetic insights and translational implications - Wasik, Mariusz A.; Kim, Patricia M.; Nejati, Reza (Frontiers in Oncology, 2024)
While normal B- and T-lymphocytes require antigenic ligands to become activated via their B- and T-cell receptors (BCR and TCR, respectively), B- and T-cell lymphomas show the broad spectrum of cell activation mechanisms regarding their dependence on BCR or TCR signaling, including loss of such dependence. These mechanisms are generally better understood and characterized for B-cell than for T-cell lymphomas. While some lymphomas, particularly the indolent, low-grade ones remain antigen-driven, other retain dependence on activation of their antigen receptors seemingly in an antigen-independent manner with activating mutations of the receptors playing a role. A large group of lymphomas, however, displays complete antigen receptor independence, which can develop gradually, in a stepwise manner or abruptly, through involvement of powerful oncogenes. Whereas some of the lymphomas undergo activating mutations of genes encoding proteins involved in signaling cascades downstream of the antigen-receptors, others employ activation mechanisms capable of substituting for these BCR- or TCR-dependent signaling pathways, including reliance on signaling pathways physiologically activated by cytokines. Finally, lymphomas can develop cell-lineage infidelity and in the extreme cases drastically rewire their cell activation mechanisms and engage receptors and signaling pathways physiologically active in hematopoietic stem cells or non-lymphoid cells. Such profound reprograming may involve partial cell dedifferentiation or transdifferentiation towards histocytes, dendritic, or mesodermal cells with various degree of cell maturation along these lineages. In this review, we elaborate on these diverse pathogenic mechanisms underlying cell plasticity and signaling reprogramming as well as discuss the related diagnostic and therapeutic implications and challenges.